Folk Sign as an Object of Linguistic Research - Toshmatova Nazokat Akramovna (Researchparks Publishing, 2022)
Various ideas that are expressed in order to explain what is happening today in our environment are called superstitious signs, linguoculturology is the study of differences and similarities between space and time.